Prenatal Yoga - Farida Tandi Bara (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Pregnancy is a physiological condition. During pregnancy there is discomfort which is a result of the physiological adaptation process of the mother's body system to her pregnancy. Discomfort that is still within normal limits can turn out to be abnormal due to the mother's unpreparedness for her pregnancy. Healthy pregnant women will have an impact on optimal fetal development. Labor preparation also starts from pregnancy. Prental yoga is a promotive and preventive effort to improve the health of the mother so that she can adapt to physical and psychological changes during pregnancy and prepare for labor. Prenatal yoga join by pregnant women starting from the second trimester, done every Tuesday and Friday for 90 minutes. Each session starts with pranayama (breathing) practice, asana practice and kegel exercise. At the end, a relaxation and positive affirmation exercise was carried out. The results achieved in this activity are (1) increased physical fitness of pregnant women. (2) increasing the psychological readiness of mothers.